Different developmental histories of beta-cells generate functional and proliferative heterogeneity during islet growth - Sumeet Pal Singh (Nature Portfolio, 2017)
Βeta-cells have recently been shown to be heterogeneous with regard to morphology and function. Here, the authors show that β-cells in zebrafish switch from proliferative to functional states with increasing time since β-cell birth, leading to functional and proliferative heterogeneity.